Reconstructing Childhood via Reimagined Memories: Life Writing in Children’s Literature - Emma-Louise Silva (Literature)
For authors who revisit their experiences of childhood to write stories for young readers, imaginatively drawing on memories plays a prominent role in the creative process. Whereas connections between memories and narratives have featured in literary studies and children’s literature studies, the unfolding of negotiations between memory and imagination as authors create narratives of life writing is underexplored. This article examines how negotiations of memory and imagination unfold on paper during the writing processes for Roald Dahl’s Boy (1984), David Almond’s Counting Stars (2000), and Jacqueline Woodson’s Brown Girl Dreaming (2014). While positioning itself in the field of cognitive literary studies and the archival study of creative writing processes, this article aims to generate insights on the reconstructive approach to memory, which considers episodic remembering as imagining the past. By transposing the study of the dynamics of writing processes, or genetic criticism, to children’s literature, I explore notes, mindmaps, manuscripts, and typescripts held at the archives of Dahl, Almond, and Woodson to chart how they imaginatively incorporate memories of their youth into their life writing. As such, this research informs understandings of the narrative genesis of the authors’ works, while drawing on the manifestations of their literary creativity in an attempt to broaden knowledge regarding memory and imagination.